Market Reaction to the Latest Appointment of The Finance Minister: Empirical Evidence Through Abnormal Return, Trading Activity and Stock Volatility on The LQ45 Index - I Ketut Tri Anansa; Siti Aisyah Hidayati; Nila Rahayu (Economics and Business Journal (ECBIS), 2026)
This study examines the Indonesian capital market reaction to the announcement of the appointment of Purbaya Yudhi Sadewa as Minister of Finance on September 8, 2025. Using an event study approach, the analysis focuses on companies included in the LQ45 index and observes market reaction within an eleven-day event window from five trading days before to five trading days after the announcement. Market reaction is measured using abnormal return, trading volume activity, and stock volatility. The data consist of daily stock prices, trading volume, outstanding shares, and market index data obtained from capital market data sources. Because the normality test indicates that the data are not normally distributed, the hypotheses are tested using the Wilcoxon Signed Rank Test. The findings show significant differences in abnormal return, trading volume activity, and stock volatility before and after the announcement. These results indicate that the appointment of the Minister of Finance contains information value for investors and is associated with changes in price reaction, trading intensity, and perceived market risk among LQ45 stocks. The study contributes to event study literature by documenting market responses to a strategic fiscal leadership event in an emerging capital market